Life after death: the critical role of extracellular DNA in microbial biofilms. (1st August 2013) - Jakubovics, N.S.; Shields, R.C.; Rajarajan, N.; Burgess, J.G.
Abstract The death and lysis of microbial cells leads to the release of cytoplasmic contents, many of which are rapidly degraded by enzymes. However, some macromolecules survive intact and find new functions in the extracellular environment. There is now strong evidence that DNA released from cells during lysis, or sometimes by active secretion, becomes a key component of the macromolecular scaffold in many different biofilms. Enzymatic degradation of extracellular DNA can weaken the biofilm structure and release microbial cells from the surface. Many bacteria produce extracellular deoxyribonuclease (DNase) enzymes that are apparently tightly regulated to avoid excessive degradation of the biofilm matrix. Interfering with these control mechanisms, or adding exogenous DNases, could prove a potent strategy for controlling biofilm growth.